Оценка эффективности выполнения студентами заданий на компьютерных тренажерных системах по электромеханике - Черный, Алексей Петрович; Сергиенко, Сергей Анатольевич; Кравец, Алексей Михайлович; Юдина, Анна Леонидовна (Национальный технический университет "Харьковский политехнический институт", 2019)
В статье представлен метод контроля процесса выполнения студентами заданий на виртуальных стендах-тренажерах. Выполнен анализа процесса и предложены методы оценки его эффективности основе метрик расстояния. Приведены фрагменты программной реализации в LabVIEW. С использованием метрик Ейлера, Хемминга и Чебышева разработаны критерии оценивания эффективности выполнения студентом заданий на стендах-тренажёрах. Проанализировано влияние отдельных метрик на суммарный критерий оценивания. Полученные результаты позволяют количественно оценить процесс выполнения работы от «плохо» до «очень хорошо».

The article presents a method for controlling the process of students task execution on virtual test-simulators. The aim ofthe work is to assess the effectiveness of students task execution on computer-based training systems for electrical engineering; using distance metrics to determineit competencies in vocational training. An analysis of the process was performed and methods for evaluating its effectiveness based on distance metrics were proposed. Fragments of software implementation in LabVIEW were given. Using the Euler, Hemming and Chebyshev metrics, criteria was developed for evaluating the effectiveness of a student task execution on training stands. The influence of individual metrics on the total evaluation criterion was an-alyzed. The obtained results makes it possible to quantify the process of task execution from “bad” to “very good” and allows, to track the sequence of actions performed by students in carrying out laboratory work on the laboratory virtual training stands. According to the recorded events, the teacher can assess the degree of readiness of the student to work with real physical equipment, and also point out to him the mistakes made in the process of working with a virtual stand. The developed criteria allow to analyze the progress of the work, give an idea of the nature of the student’s actions and the degree of their correctness.
Evaluation of the efficiency of the execute of students tasks on computer training systems in the subject «electromechanics»
Keywords: виртуальный стенд-тренажёр; контроль процесса; метрики расстояния; virtual training stands; process control; distance metrics